Ubiquitylation regulates interactions of astral microtubules with the cleavage apparatus - Kammerer, Daniel; Stevermann, Lea; Liakopoulos, Dimitris (Current biology, 2010)
Correct positioning of the mitotic spindle relative to the cleavage apparatus is crucial for successful mitosis. In budding yeast, the Adenomatous Polyposis Coli-related protein Kar9, yeast EB1, and Myo2, a type V myosin, mediate positioning of the mitotic spindle close to the septin-anchored cleavage apparatus at the bud neck.